1997
DOI: 10.1016/s0014-5793(97)00185-3
|View full text |Cite
|
Sign up to set email alerts
|

Prooxidant activity of caffeic acid, dietary non‐flavonoid phenolic acid, on Cu2+‐induced low density lipoprotein oxidation

Abstract: © 1997 Federation of European Biochemical Societies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 28 publications
6
46
2
Order By: Relevance
“…Redox cycling of HCAs can be catalyzed by transition metals in the presence of oxygen, producing organic radicals along with ROS that may damage biological macromolecules [160].…”
Section: Pro-oxidant Effects Of Hydroxycinnamic Acidsmentioning
confidence: 99%
“…Redox cycling of HCAs can be catalyzed by transition metals in the presence of oxygen, producing organic radicals along with ROS that may damage biological macromolecules [160].…”
Section: Pro-oxidant Effects Of Hydroxycinnamic Acidsmentioning
confidence: 99%
“…The phytoestrogens and their metabolites have many potent hormonal and non-hormonal activities that may explain some of the biological effects of diets rich in isoflavones (Mazur et al, 1998;Setchell, 1998;Song et al, 1999;Ren et al, 2001;Arjmandi & Smith, 2002). On the other hand, depending on the concentration and hydroxyl substituent pattern, phenolic compounds can also act as pro-oxidants (Laughton et al, 1989;Yamanaka et al, 1997;Metodiewa et al, 1999). Other negative physiological effects of flavonoids (mutagenicity, genotoxicity, cytotoxicity) have also been described (MacGregor & Jurd, 1978;Brown & Dietrich, 1979;Brown, 1980;Rueff et al, 1992;Yamanaka et al, 1997;Metodiewa et al, 1999;Hodek et al, 2002).…”
Section: Structure Classification Distribution Of Phenols In Plant mentioning
confidence: 99%
“…On the other hand, depending on the concentration and hydroxyl substituent pattern, phenolic compounds can also act as pro-oxidants (Laughton et al, 1989;Yamanaka et al, 1997;Metodiewa et al, 1999). Other negative physiological effects of flavonoids (mutagenicity, genotoxicity, cytotoxicity) have also been described (MacGregor & Jurd, 1978;Brown & Dietrich, 1979;Brown, 1980;Rueff et al, 1992;Yamanaka et al, 1997;Metodiewa et al, 1999;Hodek et al, 2002). Most of these physiological effects are based on either in vitro models, cell/tissue culture studies, animal experiments or epidemiological data.…”
Section: Structure Classification Distribution Of Phenols In Plant mentioning
confidence: 99%
“…It is not known whether this mechanism can occur with other classical antioxidants, such as uric acid, although evidence has been obtained indicating that free radical metabolites originate from the oxidation of uric acid [17] and that the combination of Cu(II) and uric acid may promote oxidative DNA breakage [18]. Moreover, studies performed with other water-soluble antioxidants, such as Trolox C [19], ascorbic acid [20], caffeic acid [21] and green tea cathechins [22], have revealed that these compound may act either as antioxidants or pro-oxidants during copper-mediated LDL oxidation.…”
Section: Introductionmentioning
confidence: 99%